Agricutural-Based Adsorbents For Methylene Blue Adsorption: Equilibrium, Kinetic And Thermodynamics Studies - Rudrusamy, Krishnaveni (2009)

(untitled)
This study focuses on the removal of cationic dye (methylene blue) from aqueous solution using agricultural waste as alternative adsorbents. The main aim of this study was to investigate the adsorption of methylene blue (MB) onto durian peel (DP), banana leaves (BL), pineapple stem (PPS), pineapple leaves (PPL), papaya stem (PYS) and papaya leaves (PYL). The effects of operating conditions such as initial dye concentration (50-500 mg/L), contact time, pH (2-10) effect, and temperature (30-50 oC) on adsorption of MB were studied in batch process. Equilibrium data for the adsorption of MB on all the adsorbents were analyzed by the Langmuir, Freundlich and Tempkin isotherm models. It was found that Langmuir isotherm model fits the data very well for all the adsorbents. Pseudo-first-order, pseudo-second-order and intraparticle diffusion were tested to investigate the adsorption mechanism.